Nano edible coatings and their applications in food preservation - Mahela, Unique; Rana, D K; Joshi, Udit; Tariyal, Yashwant Singh (Journal of Postharvest Technology, 2020)
Due to a lack of adequate infrastructure and limited use of modern postharvest technologies, 20 to 30% of the produce is lost annually. Using nano edible coatings is among the suitable ways for preserving food characteristics at reasonable costs. For increasing the shelf life of food articles, a very  thin layer is created on their surface. In a nanosystem, in contrast to a larger particle system, materials are supplied with improved and distinct properties.  The shelf life of many products like fresh vegetables and fruits, nuts, etc., gets increased by this technology via the incorporation of substances having  hydrophilic, antimicrobial, and antioxidant properties. The substances are generally released during storage periods of the food products. Different  nanocoatings are nanoemulsion, polymeric nanoparticles, solid lipid nanoparticles, lipid nanocarriers, nanotubes, nanofibers, etc. Besides several  advantages, some nanocoatings might carry allergic properties associated with them and also are economically not viable to use. Nanosystems  nowadays are gaining a lot of importance in food preservation-related research areas, and their development as efficient edible coatings offer great  potential in the relevant fields. Hence, there is a need for more research work to apply the nanoparticles and their consumption perspective.
Keywords: Antimicrobial; , food,; nanoparticles; postharvest; shelf life